Household income differences in food sources and food items purchased - Wall Melanie; French Simone A; Mitchell Nathan R (BMC, 2010)
Abstract Background The present study examined income-related household food purchases among a sample of 90 households from the community. Methods Annotated food purchase receipts were collected for a four-week period by the primary household shopper. Receipt food source and foods items were classified into specific categories, and food quantities in ounces were recorded by research staff. For home sources, a limited number of food/beverage categories were recorded. For eating out sources, all food/beverage items were recorded. Median monthly per person dollars spent and per person ounces purchased were computed. Food sources and food categories were examined by household income tertile. Subjects and Setting A community-based sample of 90 households. Results Higher income households spent significantly more dollars per person per month from both home and eating out sources compared with lower income households ($163 versus $100, p < .001). Compared with lower income households, higher income households spent significantly more home source dollars on both fruits/vegetables (21.5 versus 10.2, p < .001) and sweets/snacks (17.3 versus 8.3, p < .001), but did not differ on home dollars spent on sugar sweetened beverages (2.0 versus 1.7, p < .46). The proportion of home beverages that were sugar sweetened beverages was significantly higher among lower income households (45% versus 26%, p < .01). Within eating out sources, lower income households spent a significantly greater percent of dollars per person at carry out places (54% versus 37%, p < .01). No income differences were observed for dollars spent at discount grocery stores, small grocery stores or convenience stores. Conclusions Higher income households spent more money on both healthy and less healthy foods from a wide range of sources. Lower income households spent a larger proportion of their eating out dollars at carry out places, and a larger proportion of their home beverage purchases were sugar sweetened beverages.